2005
DOI: 10.1242/jcs.01636
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of early biphasic activation of poly(ADP-ribose) polymerase-1 in response to ultraviolet B radiation

Abstract: The damage to DNA caused by ultraviolet B radiation (280-320 nm) contributes significantly to development of sunlight-induced skin cancers. The susceptibility of mice to ultraviolet B-induced skin carcinogenesis is increased by an inhibitor of the DNA damage-activated nuclear enzyme poly(ADP-ribose) polymerase-1 (PARP), hence PARP activation is likely to be associated with cellular responses that suppress carcinogenesis. To understand the role of activated PARP in these cellular functions, we need to first cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
56
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 59 publications
9
56
0
3
Order By: Relevance
“…PARP plays a role in the recognition of DNA damage, and it works synergistically with NER enzymes (46)(47)(48). Lysates derived from MyD88 2/2 (but not WT) PMs maintained functional PARP activity (ADP-ribosylate histones in vitro) (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…PARP plays a role in the recognition of DNA damage, and it works synergistically with NER enzymes (46)(47)(48). Lysates derived from MyD88 2/2 (but not WT) PMs maintained functional PARP activity (ADP-ribosylate histones in vitro) (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Global and local UVC irradiation of cells has been reported (9). The repair kinetics assays for T-T and 6-4PP in cellular genomic DNA by flow cytometry and immunofluorescence microscopy and detection of NER proteins after local irradiation are detailed in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…We showed earlier that PARP-1 rapidly binds to UV-damaged DNA in vitro or in UV-irradiated cells, and it is activated to form PAR within seconds after irradiation at the site of DNA damage (9). Because DDB2, the early GG-NER protein, is also known to translocate very rapidly at the site of UV-damaged DNA (16), we examined whether DDB2 and PARP-1 interact with each other in the vicinity of UV-damaged chromatin using cellular fractions that represent chromatin-bound proteins (Chfraction) rather than the whole cell extract in coimmunoprecipitation (co-IP) studies (Fig.…”
Section: Parp Inhibitors Delaymentioning
confidence: 99%
“…We have earlier shown that PARP-1 binds to UV-damaged large oligonucleotide in vitro or to chromatin fragments containing T-T lesions in vivo 11 . We also showed that PARP-1 and DDB2 associate with each other on the chromatin of UV-irradiated cells and that DDB2 stimulates catalytic activity of PARP-1 in the presence of UV-damaged DNA 7 .…”
mentioning
confidence: 99%